Why Us?! How Members of Minority Groups React to Public Health Advertisements Featuring Their Own Group. (July 2019) - El Hazzouri, Mohammed; Hamilton, Leah K.
This research investigates how members of minority groups respond to public health advertising that features models who belong to their own group. Results of three experiments show that ethnic minority individuals report lower intentions to take the advice solicited by widely distributed public health advertisements when the advertisements feature models who belong to their own ethnic group (as opposed to white models). This effect is driven by the fact that, for ethnic minorities, featuring one's own ethnic group in public health advertising creates perceptions of being negatively stereotyped by the advertisers. This outcome is pronounced for those with average and high stigma consciousness. These effects were generalized in a fourth experiment in which participants with obesity reacted negatively to public health advertising featuring obese models. Public health advertising featuring minorities does not generate this backlash effect when the advertising appears in community-based publications mostly read by the featured group.